Этимологии удмуртских слов : : [словарь] / В. И. Вершинин - Вершинин Валерий Иванович (Курсив, 2015)
Экземпляры: РБ (20220325) / Инвентарный номер: 63421 / Цена: 200.00 / Авт.знак: В 37 / ГРНТИ: 16 / ББК: 81(2Рос.Удм)-4